Fungsionalisme Makna Simbolik Tradisi Ngampirne Weton - Susilo, Ariani; Sapto, Ari; Yudo, Deny; Agung, Dewa (Jayapangus Press, 2025)
This research is motivated by the need to understand the meaning of the symbols contained in the ngampirne weton tradition. So that its role is considered as a symbol of unity and social solidarity as a means to share sustenance and strengthen social relations. This study aims to understand the symbolic meaning and function of the Ngampirne Weton tradition in Semen Village, Blitar Regency, East Java, as well as the community's views on this tradition. The ngampirne weton tradition is a tradition of commemorating someone's birthday based on the Javanese calendar by holding a thanksgiving. The research method used is qualitative with an ethnographic model, data collection through literature studies, in-depth interviews, participant observation, and documentation collection. The results of the study show that the ngampirne weton tradition contains symbolic meaning in every dish served. The foods that are symbols of this tradition are golong pithu, apem, buceng, porridge and asahan sekul sayur sakaturan. The community believes that carrying out the ngampirne weton tradition is a means of expressing gratitude, praying for safety, respecting ancestors and warding off bad luck. In addition to these beliefs, the community interprets it as a glue for cultural and community identity. Based on the research, it was found that the function of the ngampirne weton tradition is as a) religion, b) social balance c) strengthening cultural identity. Positive meanings and teachings are found in this tradition, including asking for safety and blessings from God Almighty, teaching to share with others through slametan, not only that, the value of gratitude, mutual cooperation is also manifested in the slametan. Understanding the meaning in each symbol of the ngampirne neton tradition needs to be done, by understanding it can be known the function of a meaning.